1999
DOI: 10.2166/wst.1999.0549
|View full text |Cite
|
Sign up to set email alerts
|

Development of the heavy metal pollution trends in several European rivers: an analysis of point and diffuse sources

Abstract: A comparison has been made between the metal pollution in several European rivers in various stages of clean-up and management for the period of 1980-1996. The investigated rivers were Rhine, Meuse, Scheldt, Weser and Elbe. The results from this comparison showed that the simple statement that characterizes the river Elbe as ‘the most polluted river in Europe’ is a simplification. Three independent methods are presented to estimate point and diffuse source contributions in emissions and riverine transports. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
34
0
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 0 publications
0
34
0
2
Order By: Relevance
“…However, at present their greatest concentration is due to human activity, namely mining, agriculture, industrial processes and household waste 9 . Therefore, an important part of the heavy metals in the water may be related to human activities 10,11 . This human activity has often led to the transformation of the water of rivers, lakes and coasts into waste deposits; natural balance is severely disturbed and in many cases totally lost 4 .…”
Section: Introductionmentioning
confidence: 99%
“…However, at present their greatest concentration is due to human activity, namely mining, agriculture, industrial processes and household waste 9 . Therefore, an important part of the heavy metals in the water may be related to human activities 10,11 . This human activity has often led to the transformation of the water of rivers, lakes and coasts into waste deposits; natural balance is severely disturbed and in many cases totally lost 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Cd, Cr, Cu, Hg, Ni, Pb and Zn), due to the deposition of contaminated sediments during flooding events in the past (Schröder, 2005). The sediments were especially contaminated in the 1960s and 1970s, due to unbridled emissions and a lack of integrated water pollution control (Vink et al, 1999;Middelkoop, 2000). Especially Zn, Cu, Pb and Cd are present in levels posing risks towards floodplain ecosystems (Kooistra et al, 2001Leuven et al, 2005;Van Vliet et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…At the end of the twentieth century river sediment studies in Western Europe showed that heavy metal concentrations began to decline (Vink et al, 1999;Middelkoop, 2002). At the end of the Cold War most of the former industrial plants were closed, modern waste water treatment systems started to be installed, those factors may have contributed to the decline of concentrations (Scherer et al, 2003;Zerling et al, 2006) while in the Eastern Europe and Asia the situation remains different.…”
Section: Introduction 1)mentioning
confidence: 99%